2018
DOI: 10.1186/s12888-018-1783-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric diagnoses in asylum seekers with follow-up

Abstract: BackgroundIn the study, the frequency and nature of asylum seekers’ psychiatric diagnoses in a German admission center were examined. Additional aims were to identify changes in those diagnoses over time and to investigate health care utilization of mentally ill asylum seekers in the community.MethodsThe sample for the study “Psychiatric Examination of Asylum Seekers” in Bavaria consisted of a total of 283 asylum seekers and included 2 subsamples: help-seeking individuals and a randomly selected group. 34 of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 27 publications
2
42
0
7
Order By: Relevance
“…All were observational, except one RCT from which we included baseline prevalence data [24]. Studies were undertaken in 15 countries: Australia (652 refugees) [33][34][35][36][37], Austria (150) [38], China (65) [32], Germany (1,104) [39][40][41][42][43][44], Italy (297) [39], Lebanon (646) [45,46], Nepal (574) [25], Norway (64) [23], South Korea (200) [47], Sweden (86) [48], Switzerland (164) [49,50], Turkey (238) [51], Uganda (77) [24], UK (420) [39,52], and the US (406) [31,53]. Participants were from four geographic regions: the Middle East (43%), Europe (29%), Asia (20%), and Africa (5%), with two studies reporting refugee samples coming from 18 different countries (3%) [26,41] (97% of total sample due to unreported countries of origin).…”
Section: Plos Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…All were observational, except one RCT from which we included baseline prevalence data [24]. Studies were undertaken in 15 countries: Australia (652 refugees) [33][34][35][36][37], Austria (150) [38], China (65) [32], Germany (1,104) [39][40][41][42][43][44], Italy (297) [39], Lebanon (646) [45,46], Nepal (574) [25], Norway (64) [23], South Korea (200) [47], Sweden (86) [48], Switzerland (164) [49,50], Turkey (238) [51], Uganda (77) [24], UK (420) [39,52], and the US (406) [31,53]. Participants were from four geographic regions: the Middle East (43%), Europe (29%), Asia (20%), and Africa (5%), with two studies reporting refugee samples coming from 18 different countries (3%) [26,41] (97% of total sample due to unreported countries of origin).…”
Section: Plos Medicinementioning
confidence: 99%
“…Six studies of psychotic illness were identified (n = 1,695) [23,31,36,39,43,45]. Participants had a weighted mean age of 37.6 years and 51% were female.…”
Section: Plos Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, findings indicate an increased burden of mental disorders among refugees and asylum seekers [3][4][5][6], also when compared to non-refugee immigrants [7,8]. The prevalence of post-traumatic stress disorder (PTSD) is reported to be significantly higher in refugees compared to the general population [3,9,10]. For example, most studies assessing PTSD prevalence, predominantly conducted in Western countries, report either estimates of 20% and above [5] or a tenfold risk compared to the majority [3].…”
Section: Introductionmentioning
confidence: 99%
“…Vor allem in den arabischsprachigen Ländern des Nahen Ostens wie Syrien, dem Libanon, Irak, Israel und Palästina führen anhaltende Konflikte und eine daraus resultierende Migration und Flucht zu immensen psychischen Beeinträchtigungen der Bevölkerung in den Heimat-und Aufnahmeländern [1]. Während die Datenlage zu den Prävalenzraten von psychischen Störungen der arabischsprachigen Bevölkerung noch sehr lückenhaft ist, zeigen Studien mit arabischsprachigen Geflüchteten in Deutschland deutlich erhöhte Prävalenzraten für das Auftreten einer psychischen Störung von 30 -95 % [3][4][5]. Zu den häufigsten Störungen in dieser Population zählen posttraumatische Belastungsstörungen mit Prävalenzschätzungen zwischen 29 und 81 %, Depressionen (14 -88 %) und Angststörungen (27 -92 %) (für einen Überblick siehe Winkler et al [6]).…”
Section: Introductionunclassified